The effect of carbohydrate mouth rinse on performance, biochemical and psychophysiological variables during a cycling time trial: a crossover randomized trial - Amanda M. J. Ferreira; Luiz F. Farias-Junior; Thaynan A. A. Mota; Hassan M. Elsangedy; Aline Marcadenti; Telma M. A. M. Lemos; Alexandre H. Okano; Ana P. T. Fayh (Taylor & Francis Group, 2018)
Background The hypothesis of the central effect of carbohydrate mouth rinse (CMR) on performance improvement in a fed state has not been established, and its psychophysiological responses have not yet been described. The aim of this study was to evaluate the effect of CMR in athletes fed state on performance, biochemical and psychophysiological responses compared to ad libitum water intake. Methods Eleven trained male cyclists completed a randomized, crossover trial, which consisted of a 30 km cycle ergometer at self-selected intensity and in a fed state. Subjects were under random influence of the following interventions: CMR with a 6% unflavored maltodextrin solution; mouth rinsing with a placebo solution (PMR); drinking "ad libitum" (DAL). The time for completion of the test (min), heart rate (bpm) and power (watts), rating of perceived exertion (RPE), affective response, blood glucose (mg/dL) and lactate (mmol/DL), were evaluated before, during and immediately after the test, while insulin (uIL/mL), cortisol (μg/dL) and creatine kinase (U/L) levels were measured before, immediately after the test and 30 min after the test. Results Time for completion of the 30 km trial did not differ significantly among CMR, PMR and DAL interventions (means = 54.5 ± 2.9, 54.7 ± 2.9 and 54.5 ± 2.5 min, respectively; p = 0.82). RPE and affective response were higher in DAL intervention (p < 0.01). Glucose, insulin, cortisol and creatine kinase responses showed no significant difference among interventions. Conclusions In a fed state, CMR has not caused metabolic changes, and it has not improved physical performance compared to ad libitum water intake, but demonstrated a possible central effect. ReBec registration number: RBR-4vpwkg. Available in http://www.ensaiosclinicos.gov.br/rg/?q=RBR-4vpwkg.